Komunikasi Asik Keluarga di Tengah Pandemi - Dartina, Vina Dartina (Ma'soem University, 2021)
The variety of conflicts or friction that occurs in the family causes social interactions in the family to experience dynamics. The COVID-19 pandemic teaches us to understand how family communication management should be. Each family entity must be understand its roles and responsibilities. A father must know his role as a good father and family leader. Likewise, mothers must know their role as a wife and biological mother for their children. Likewise, a child must know what his role is as a child of both parents. In collaboration with Young Living Indonesia, the author conducted a 1-day webinar as an effort to provide training related to communication within the family. The communication approach in the family that is carried out refers to the aspects of interpersonal communication of family members, namely openness, empathy, support, positive feelings, and equality. The method used in solving communication problems in the family is through online counseling or webinars which aim to increase understanding and awareness of the importance of building communication within the family. The results of this webinar include participants starting to realize that by building communication, they can improve and improve the quality of family life, which will be followed up by directly practicing what is conveyed in the webinar in their respective families.